Analysis of physiological characteristics and gene co-expression networks in Medicago sativa roots under low-temperature stress - Wang, Xiaolong; Chai, Hua; Xu, Yanxia; Li, Shasha; Wu, Yue; Wang, Ruoding; Yang, Zhao (Frontiers in Plant Science, 2025)
Medicago sativa is the most widely cultivated high-protein forage crop globally. However, its cultivation in high-latitude and cold regions of China is significantly hindered by low-temperature stress, particularly impacting the root system, the primary functional tissue crucial for winter survival. The physiological and molecular mechanisms underlying the root system’s adaptation and tolerance to low temperatures remain poorly understood. To this end, this study utilized cold-tolerant Medicago sativa “Lomgmu801” and the cold-sensitive Medicago sativa “Sardi” genotypes as experimental materials to investigate root physiological responses during the overwintering period. Physiological indices, including soluble sugars (SS), proline (Pro), glutathione (GSH), jasmonic acid (JA), abscisic acid (ABA) contents, and peroxidase (POD) activity, were quantified. RNA-seq revealed 743 differentially expressed genes (DEGs) between the cold-tolerant and sensitive genotypes. Subsequently, correlation analysis between DEGs and physiological indices revealed that DEGs in the yellow, blue, and turquoise modules were significantly correlated with the levels of POD, GSH, SS, Pro, JA, and ABA. The core genes were predominantly included in the “MAPK signaling pathway”, “glutathione metabolism”, “plant hormone signal transduction”, “arginine and proline metabolism”, and “phenylpropanoid biosynthesis”. Ultimately, DEGs responsive to low-temperature stress were identified, including MsGST, MsRboh, MsPOD, MsJAZ, MsP5CR, and MsPP2C. By integrating physiological characteristics with cold-tolerance-associated genes, this study elucidates the physiological and molecular mechanisms underlying Medicago sativa root adaptation to low temperatures. The RNA-seq data and the core DEGs identified provide valuable theoretical insights and targets for future molecular breeding efforts aimed at enhancing cold tolerance in Medicago sativa.